STUDI KOMPARASI AL-GORITMA KEAMANAN DATA MENGGUNAKAN KRIPTOGRAFI VIGENERE CHIPER DAN RIVEST SHAMIR ADLEMAN (RSA) - Ii Sopiandi; Abdul Jabbar (Universitas Majalengka, 2020)
This study aims to compare empirically the cryptographic Vigenere Chiper and Rivest Shamir Adleman (RSA) using the Waterfall methodology based on this research in terms of Encryption and Decryption, in terms of time (seconds) to find out how long the encryption and decryption time is, the researchers prepare 10 ( ten) TXT file types with different sizes and compared to the average amount of time obtained. Understanding Cryptography According to Experts Cryptography is the science and art of securely storing messages, data or information. Cryptography comes from the Greek word Crypto and Graphia which means secret writing. Cryptography is a science that studies writing in secret. Cryptography is part of a branch of mathematics called Cryptology.